The Role of Genetic Testing in Palliative Care Decisions for Critically Ill Newborns - Ashley Mowery; Luca Brunelli (Children)
Genetic testing is rapidly becoming standard practice in the care of critically ill newborns within NICUs. Numerous studies have demonstrated the utility of genetic testing, including changes in clinical care, improved diagnostic certainty, and cost savings, related to a reduced length of hospital stay. Changes in clinical management reported in previous studies also included redirection to comfort or end-of-life care. However, it has been difficult to study the influence of genetic testing in the redirection of care decisions within the NICU because of the complexity of the medical decision-making process. Redirection of care decisions are deeply personal for each individual family and often must be made in the setting of clinical instability and diagnostic and prognostic uncertainty. A recent study exploring the impact of genetic testing in redirection of care decisions by surveying palliative care providers suggested genetic testing plays a minor role in decisions to redirect to end-of-life care or in the implementation of DNR/DNI orders. However, factors such inadequate treatment options were found to be important in redirection of care decisions, implying the need for further investigation to clarify the role of genetic testing. Future studies will need to focus on how genetic information affects healthcare provider recommendations regarding palliative care and how families use this information to make end-of-life care decisions.